Military economics the interaction of power and money - Smith, Ron (Palgrave Macmillan, 2009)
"Military power needs to be financed and economic development is often shaped by military conflict, thus the interaction of military and economy, power and money is central to the modern world. This book provides an accessible introduction to the economics of the use of organised force, with a wide range of historical and current examples"--Provided by publisher